Chapter 2. Criminal and Criminological aspects about act N˚18.987 which legalize the abortion in Uruguay - Montano, Pedro J (Journal international de bioéthique et d'éthique des sciences, 2019)
After Cuba, Uruguay is the first country that has adopted a legal regime which allows the abortion. The law is from November 2012 and has presented problems for its interpretation and implementation. Was a correct solution for Uruguay? Were not other alternatives more convenient to be tried before? The author exposes different measures to be taken, that can avoid the abortion from its roots, as well as the effect produced by permissive laws. He also presents the role to be accomplish by Criminal Law in relation with the subject, and if the Uruguayan law has created a new cause of justification, a new right, or a new cause of impunity The abortion can be considered a woman’s right? or should we talk about a family right? In the law, it is practically denied the participation of the father of the child, consequently it is transformed as a new instrument for family/domestic violence.